PEMANFAATAN SISA TANAMAN SAYURAN SEBAGAI KOMPONEN COMPLETE FEED TERFERMENTASI TERHADAP UREA DARAH DAN RETENSI NITROGEN DOMBA - Murniastuti, Hikmah Yuli; Sutrisno, Sutrisno; Pangestu, Eko (Animal Agriculture Journal, 2012)
Vegetable plant residues (VPR) potential as a source of feed for ruminants.The study was conducted to the utilization of vegetable plant residues as a grassfor component complete feed fermentation on the blood urea and nitrogenretention in sheep. This research was conducted in a randomized block design(body weight as a blok) with 5 treatment, 4 replication. This study used 20 head ofsheep with an average body weight 10,5 Â± 1,73 kg, which is divided into 5treatment rations, namely T1 : 50% VPR + 50% concentrate, T2 : 37,5% VPR +12,5% grass + 50% concentrate, T3 : 25% VPR + 25% grass + 50% concentrate,T4 : 12,5% VPR + 37,5% grass + 50% concentrate, T5 : 50% grass + 50%concentrate. The result showed no significant effect of replacing grass withvegetable plant residues on the blood urea and nitrogen retention in sheep. Theresult can be concluded that VPR can be given and subtitute grass in completefeed to offer level 50%.Keywords: vegetable plant residues, blood urea, nitrogen retention